A molecular dynamics investigation of the micro-mechanism for vacancy formation between Ag3Sn and βSn under electromigration. (2nd January 2018) - Zhang, Jicheng; Yang, Jian; Liang, Lihua; Xu, Yangjian; Guo, Jing
ABSTRACT: In this paper, the vacancy formation at the interface between different grains (Ag3 Sn and βSn) induced by electromigration was investigated from the perspective of atom diffusion. To explain the micro-mechanism of void formation near the interface, the diffusion coefficient was specifically studied here via molecular dynamics (MD) simulation. By comparing the atom diffusion rates of atoms in βSn and Ag3 Sn, a significant difference could be observed when the temperature is up to 400 K. The Sn atoms in βSn have a higher diffusion coefficient (8E − 9 cm 2 /s) than atoms in Ag3 Sn (4E − 9 cm 2 /s), which indicated that the void would be prone to appear in βSn near the interface. Moreover, the effect of grain size and pressure on atom diffusivity was studied. Results show that the atom diffusivity depends heavily on the grain size of Ag3 Sn. When the thickness of Ag3 Sn is increased from 4 to 12 nm, this difference is significant when the temperature is only 375 K. On the other hand, the atom diffusion character of Ag3 Sn and βSn changes substantially under constant pressure. The difference of the atom diffusion rate would be inhibited by pressure perpendicular to the interface, which indicated voids have less possibility to appear herein. Abstract :